2022
DOI: 10.1155/2022/8654449
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of CICARE Communication Mode on Disease Uncertainty, Self-Nursing Ability, and Quality of Life in Patients with Coronary Atherosclerotic Heart Disease after Percutaneous Coronary Intervention

Abstract: Objective. To study the effect of CICARE (Connect, Introduce, Communicate, Ask, Respond, Exit) communication mode on disease uncertainty, self-nursing ability, and quality of life in patients with coronary atherosclerotic heart disease (CAD) after percutaneous coronary intervention (PCI). Methods. From January 2021 to December 2021, 102 patients with CAD after PCI were randomly divided into a research group ( n  =51) and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After study and observation, the experiment patients more willing to speak out their demand and worries. Other studies have found the same thing[ 2 , 19 - 21 ]. CICARE communication is a mode of communication that advocates good communication that attends to the patients feelings of being respected, accepted and valued during the provision of medical services for patients, including connect, introduce, communication, ask, response and exit.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…After study and observation, the experiment patients more willing to speak out their demand and worries. Other studies have found the same thing[ 2 , 19 - 21 ]. CICARE communication is a mode of communication that advocates good communication that attends to the patients feelings of being respected, accepted and valued during the provision of medical services for patients, including connect, introduce, communication, ask, response and exit.…”
Section: Discussionsupporting
confidence: 68%
“…For example, the application value of CICARE communication mode nursing intervention in patients with coronary artery disease after percutaneous coronary intervention has demonstrated notable value. It has shown great potential in reducing disease uncertainty, improving treatment adherence, enhancing patients’ self-care abilities, and promoting both quality of life and nursing satisfaction[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, two important indicators, ejection fraction and quality of life, are often overlooked in the treatment of heart disease. Ejection fraction is a key parameter reflecting the contractile function of the heart, which is of crucial significance in assessing cardiac function and predicting the prognosis of the disease, whereas quality of life has a direct impact on the patient's daily life and ability to work, and is another important dimension in evaluating the efficacy of treatment [1].…”
Section: Background and Significance Of The Researchmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%